Outage Analysis of Orthogonal Time-Frequency Space Modulation in Nakagami-m Fading Channel - Aslandogan, Emir; Ilhan, Haci (IEEE, 2024)
Orthogonal Time-Frequency Space Modulation (OTFS) is a high-performance waveform for next-generation wireless communication systems, especially in cases of rapidly changing channel conditions. It is necessary to investigate the OTFS modulation under different channel models. In this study, it is assumed that the channel responses are characterized by a Nakagami-m distribution and the fading parameters are integers. We derive a outage probability expression for single-input, single-output (SISO) OTFS system using Erlang's probability density function (PDF). In addition, we analyzed the outage performance of the system according to the fading parameter and target rate. As a result, it was noted that the simulation results validated the theoretical results.
Keywords: OTFS modulation; Nakagami-m fading; outage probability; Erlang PDFs; COMMUNICATION; Computer Science; Engineering; Telecommunications